The effects of dividend, earning, cash flow and firm size on stock returns of public listed companies in Sarawak - Zulhan, Bin Matlin (Universiti Malaysia Sarawak, (UNIMAS), 2012)
There are many factors that can influence the stock return. The main objective of this study is to investigate and to evaluate the effects of dividend, earnings, cash flow and firm size on stock returns of Public Listed Companies in Sarawak which consist of 15 companies for the period of 10 yearv Correlation -Regression analysis is used to investigate the relationship between independent variables and dependent variable. The result showed that dividend has a significant negative correlation effect on the stock return. The earning and stock return has a significant positive correlation. While cash flow from operating activities and firm size showed a not significant positive correlation on stock return.